Numerical and experimental pressure determination in the very near field of a piezoelectric transducer - Filipczyński, L.; Kujawska, T.; Wójcik, J.; Tymkiewicz, R. (Archives of Acoustics, 2001)
Measurements in the very near field of piezoelectric transducers are fundamental for many ultrasonic problems. In such cases also the transducer vibrations should be known to perform mathematical models of radiated beams. Acoustic pressure measurements near to the transducer surface can give the necessary information. The pressure of the radiated wave at the transducer surface corresponds to its normal vibration velocity multiplied by the [ampersand]rho;c value of the medium. However, this is valid only for the central wave, when the edge wave of the transducer can be ignored. On the other hand, pressure measurements on and very near to the transducer surface are not possible because of the voltage leakage between the electronic transmitter and the PVDF hydrophone used in such measurements. By means of a numerical model, central and edge waves were found for a plane PZT transducer 7.5mm in radius, with the applied 2.7MHz voltage pulse composed of 3 cycles. Two types of boundary conditions of Dirichlet and Neumann were considered showing a negligible difference in the case of short pulses. Basing on numerical and experimental results, practical conditions were determined which make it possible to carry out pressure measurements in the very near field of the transducer, and hence to determine the transducer vibrations which are important for modeling ultrasonic pulse beams.